1984
DOI: 10.1111/j.1365-2125.1984.tb02354.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ascorbic acid on the sulphate conjugation of ingested noradrenaline and dopamine.

Abstract: Changes in the plasma concentration of free and conjugated noradrenaline (NA) and dopamine (DA) following oral administration of these catecholamines were examined in four normal males before and after treatment with ascorbic acid.The marked increase in plasma conijugated DA and NA was considerably reduced after ascorbic acid treatment, presumably due to competitive inhibition of sulphate conjugation. In one subject where there was a considerable delay in the appearance of sulphates, an early rise in free NA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This observation confirms previous reports in dogs and hu mans [Unger et al, 1980;Kuchel and Buu, 1981;Davidson et al, 1984]; it cannot be explained at the present time. Although an oral load of NA was shown to be associated with an increase of the plasma level of NA sulfate [Dunne et al, 1984], the intravenous route, used in the present study, is unlikely to play a major role; a decrease of NA sulfate, associated with an increase of free NA was observed in the dog after surgical stress [Un ger et al, 1980], and in humans after exercise [Davidson et al, 1984]. Furthermore, our ex perimental procedure, i.e.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This observation confirms previous reports in dogs and hu mans [Unger et al, 1980;Kuchel and Buu, 1981;Davidson et al, 1984]; it cannot be explained at the present time. Although an oral load of NA was shown to be associated with an increase of the plasma level of NA sulfate [Dunne et al, 1984], the intravenous route, used in the present study, is unlikely to play a major role; a decrease of NA sulfate, associated with an increase of free NA was observed in the dog after surgical stress [Un ger et al, 1980], and in humans after exercise [Davidson et al, 1984]. Furthermore, our ex perimental procedure, i.e.…”
Section: Discussionsupporting
confidence: 80%
“…It was the aim of the present work to investigate whether an increase of the plasma concentration of free noradrenaline (NA) was associated with an increase of that of sulfoconjugated NA. This explanation might turn out to be incomplete, because surgical stress in the dog [Unger et al, 1980] and exercise in man [Dunne et al, 1984] was shown to induce an increase of the plasma concentration of free NA and adrenaline (A), associated with a decrease of the plasma con centration of their sulfoconjugated congener. There was also a negative correlation between the plasma concentration of either NA or A and their respective degree of sulfoconjugation in patients with essential hypertension [Kuchel et al, 1981], To study the relationship between free and sulfoconjugated NA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, excess vitamins can increase the levels of monoamine neurotransmitters either by competing for the same biotransformation system or by facilitating the synthesis, or by both. Indeed, evidence shows that high doses of vitamin C decrease plasma-conjugated dopamine and norepinephrine levels by competing for sulfation [30], whereas nicotinamide increases the levels of plasma of norepinephrine [31], serotonin, and histamine [32], presumably due to a decrease in methylation-mediated degradation of the monoamines. Vitamin B 6 supplementation can increase the blood serotonin levels of newborn babies [33].…”
Section: Effect Of Vitamins On Monoamine-neurotransmitter Metabolismmentioning
confidence: 99%
“…96 Increased density of peripheral mononuclear cell D3 receptor progressing with human diastolic hypertension 97 may represent an upregulation mechanism consequent to the progressively decreasing dopaminergic function with evolution of hypertension. 46 Therapeutic interventions such as dopaminomimetic drugs 98 or prodrugs, 88 an augmentation of the renal tubular DA activity by oral calcium supplementation, 99 competitive inhibition of catecholamine sulfoconjugation by oral ascorbic acid administration making more free DA available 100 or D␤H inhibition 101 are potential strategies in modulating the free DA availability or promoting its action in hypodopaminergic hypertension. The DA 1 receptor agonist, Fenoldopam, appears to be a promising drug used i.v.…”
Section: Diagnostic and Therapeutic Implicationsmentioning
confidence: 99%